AB0633 Rituximab in scleroderma related interstitial lung disease: a single centre experience from north india. (15th June 2017) - Naidu, G; Sharma, SK; Dhir, V; Jain, S
Abstract : Background: Pulmonary involvement is one of the major causes of morbidity and mortality in patients with progressive systemic sclerosis (PSS). Clinically significant interstitial lung disease (ILD) is noted in 25% of patients and accounts for 33% of deaths in PSS patients [1, 2]. Cyclophosphamide (CYC) and mycophenolate mofetil (MMF) have been shown to retard progression of ILD [3, 4]. The limited data on rituximab indicate that rituximab might be effective in PSS related ILD [5]. Objectives: To study the efficacy of rituximab in patients with PSS related ILD. Methods: The clinical details of all patients of PSS related ILD who were treated with rituximab were noted retrospectively from the case files. Forced vital capacity (FVC) value before and 1 year after administration of rituximab were noted. Increase in FVC by 10% from baseline was considered as improvement and fall in FVC by 10% or absolute value less than 40% of predicted was considered as worsening. Patients with FVC ±10% from baseline were considered to have stabilized lung functions. Results: A total of 11 patients received rituximab between 2013 and 2016. Six (54.5%) patients were females. Median age of the subjects was 44 years (range: 31–75 years). All patients received intravenous CYC at least 1 year before rituximab administration and had either not responded to CYC or worsened after initial response to CYC. All patients received 2 doses of rituximab (1gram each) at 2 weeks interval. Median FVC before rituximab was 57% of predicted. Two patients did not have post rituximab FVC values. Median FVC 1 year after rituximab was 54% predicted. Out of the remaining 9 patients, 2 (22.2%) patients had improvement in FVC, 6 (66.7%) patients had stabilization of FVC and 1 patient worsened. One patient, who had stabilization of FVC with rituximab expired after 2 years of receiving rituximab. Conclusions: Rituximab was effective in stabilization of lung functions in patients of PSS with ILD who did not have favourable outcome with intravenous CYC. Efficacy of rituximab in treatment naive PSS related ILD patients needs to be studied. References: Tyndal AJ, Banert B, Vonk M, Airo P, Cozzi F, Carreira PE et al. Causes and risk factors for death in systemic sclerosis: a study from the EULAR Scleroderma Trials and Research (EUSTAR) database. Ann Rheum Dis. 2010; 69: 1809–152. McNearney TA, Reveille JD, Fischbach M, Friedman AW, Lisse JR, Goel N et al. Pulmonary involvement in systemic sclerosis: associations with genetic, serologic, sociodemographic and behavioral factors. Arthritis Rheum. 2007; 57: 318–26. Tashkin DP, Elashoff R, Clements PJ, Goldin J, Roth MD, Furst DEet al. Cyclophosphamide versus placebo in scleroderma lung disease. N Engl J Med. 2006;354: 2655–66. Tashkin DP, Roth MD, Clements PJ, Furst DE, Khanna D, Kleerup EC et al. Mycophenolate mofetil versus oral cyclophosphamide in scleroderma-related interstitial ling disease (SLS II): a randomised controlled, double blind, paralle group trial. Lancet Respir Med. 2016; 4: 708–19. Daoussis D, Melissaropoulos K, Sakellaropoulos G, Antonopoulos I, Markatseli TE, Simopoulou T et al. A multicenter, open-label, comparative study of B-cell depletion therapy with Rituximab for systemic sclerosis-associated interstitial lung disease. Semin Arthritis Rheum. 2016; pii: S0049–0172(16)30344–4. Disclosure of Interest: None declared